Patients with Gastrointestinal Bleeding and Atrial Fibrillation: Potential Ideal Target for Epicardial Appendage Occlusion - Stefano Branzoli; Massimiliano Marini; Domenico Catanzariti; Cecilia Pravadelli; Luigi Pannone; Giovanni D’Onghia; Mauro Fantinel; Fabrizio Guarracini; Gaia Franceschini; Mirco Zadro; Giulia Baroni; Silvia Casagrande; et al. (Journal of Cardiovascular Development and Disease)
Background: Gastrointestinal bleeding in patients with atrial fibrillation is an indication for left appendage occlusion. All endovascular devices mandate antithrombotic therapies: rebleeding risk remains an issue. To date, there are no reports on gastrointestinal rebleeding and stroke prevention by left appendage occlusion without any antithrombotic therapy in this category of patients. Methods: A total of 129 patients (male 85, mean age 76.6 ± 7.1, CHA2DS2Vasc 3.8 ± 1.5, HASBLED 3.3 ± 1.0; upper GI bleeding 10%, lower GI bleeding 86%, obscure occult 4.6%, on NOACS full dose 77.5%, NOACs reduced dose 13.1%, on anti-vitamin K 9.3%) with atrial fibrillation and history of repetitive gastrointestinal bleeding from ten centers underwent standalone thoracoscopic epicardial appendage closure without antithrombotic therapy for the entire follow up. Results: The observed bleeding rate was 0.91 events per year, equivalent to a relative risk of RR = 0.17 (p = 0.02) and a relative risk reduction (RRR) of 83%. The observed relative risk of stroke was 0.91 events per year, with a relative risk of RR = 0.19 (p = 0.03) and a relative risk reduction (RRR) of 81%. Conclusion: Standalone epicardial appendage occlusion without antithrombotic therapy in patients with repetitive gastrointestinal bleeding is safe and promising when rebleeding and stroke risk reduction need to be optimized.